2014
DOI: 10.1073/pnas.1322153111
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cellular senescence is inhibited by liver X receptor activation with an additional mechanism for its atheroprotection in diabetes

Abstract: Senescence of vascular endothelial cells leads to endothelial dysfunction and contributes to the progression of atherosclerosis. Liver X receptors (LXRs) are nuclear receptors whose activation protects against atherosclerosis by transcriptional regulation of genes important in promoting cholesterol efflux and inhibiting inflammation. Here we found that LXR activation with specific ligands reduced the increase in senescence-associated (SA) β-gal activity, a senescence marker, and reversed the decrease in telome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…showed that the activation of LXR inhibits endothelial cell senescence. Therefore, it improves endothelial dysfunction and suppresses the progression of atherosclerosis . Treatment of LXRα −/− apoE −/− mice with a synthetic LXR ligand ameliorates the cholesterol overload phenotype and reduced atherosclerosis, suggesting that LXRβ plays an important role in this procedure .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that the activation of LXR inhibits endothelial cell senescence. Therefore, it improves endothelial dysfunction and suppresses the progression of atherosclerosis . Treatment of LXRα −/− apoE −/− mice with a synthetic LXR ligand ameliorates the cholesterol overload phenotype and reduced atherosclerosis, suggesting that LXRβ plays an important role in this procedure .…”
Section: Discussionmentioning
confidence: 99%
“…Liver X receptor β represents the most important LXR isoform in endothelial cells. Activating of LXRβ prevents endothelial cellular senescence by up‐regulating the target gene sterol regulatory element binding protein‐1 . Besides, LXRβ activation reduces overproduction of reactive oxygen species and increases endothelial nitric oxide synthase activity, which stimulates the migration of endothelial cells and preserves endothelial integrity .…”
Section: Introductionmentioning
confidence: 99%
“…Belonging to the nuclear receptor superfamily, LXR transactivates genes such as ATP-binding cassette (ABC) transporters, ABCA1 and ABCG1, to promote reverse cholesterol transport (RCT) 16 . Ligand-dependent LXR activation in ECs is associated with reduced oxidative stress and increased eNOS activity 17 . Furthermore, administration of a synthetic LXR ligand to ApoE −/− or LDLR −/− mice decreased atherosclerosis 18 .…”
Section: Introductionmentioning
confidence: 99%
“…7 A role for LXRs in endothelial cell homeostasis has been previously described in which LXRs were beneficial in preventing endothelial cell activation and senescence, as well as in promoting overall endothelial health. [8][9][10] However, preservation of the endothelium is not solely mediated by direct effects on endothelial cells. Bone marrow (BM)-derived endothelial progenitor cells (EPCs) are also responsible for promoting endothelial cell maintenance.…”
mentioning
confidence: 99%